The emergence of the pandemic: High-performance coach and athlete experiences - Dehghansai, N.; Mazhar, A.; Pinder, R.; Baker, J.; Renshaw, I. (Adapted Physical Activity Quarterly, 2023)
The current study explored coach and athlete reactions and challenges leading up to the Tokyo 2020 Paralympic Games, with a specific focus on the impacts of the COVID-19 pandemic and the Games` postponement. Nine Australian Paralympic coaches (n = 3) and athletes (n = 6) shared their experiences in semistructured interviews. The thematic analysis highlighted how participants experienced the emergence of the pandemic in different ways, but all were relieved when the late but eventual decision to postpone the Games was made. Regarding lockdown periods (i.e., social-distancing restrictions), some coaches and athletes thrived under the new reality (i.e., training from home, online coaching) while others had more difficulty adjusting. Furthermore, results highlight the many uncertainties still remaining, which continue to influence participants` sport and personal lives. The experiences of coaches and athletes during the COVID-19 pandemic sheds light on strategies and resources that could support Paralympic coaches and athletes during current and future crises.